STRATEGY IN MAINTAINING BUSINESS PARTNER LOYALTY AT PT. ASKRINDO SYARIAH FINANCING GUARANTEE MEDAN BRANCH - Maryam Batubara; Khairina Tambunan; Rizkika Yulika (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to find out how the strategies that can be applied in maintaining the loyalty of business partners at PT. Askrindo Syariah Financing Guarantee Medan Branch. The research method used is for descriptive qualitative research using the SWOT analysis technique. Data collection techniques carried out are conducting interviews, questionnaires, and documentation. The results of the study indicate strategies that can be implemented to maintain business partner loyalty at PT. Askrindo Syariah Financing Guarantee in the Medan Branch is to be able to expand the promotion system carried out and the company's branches by increasing the number of competent & professional human resources or workforce and being able to establish cooperative relationships with various financial institutions, especially regional financial institutions which continue to grow steadily. Maintain the concept of Trust, Competent, Harmonious, Loyal, Adaptive and Collaborative so that the level of loyalty of business partners increases and can be maintained so that it has a greater impact and provides growth development at PT. Askrindo Syariah Financing Guarantee Medan Branch.